Dynamic tensile behaviours of heterogeneous rocks: The grain scale fracturing characteristics on strength and fragmentation. (August 2018) - Li, X.F.; Li, X.; Li, H.B.; Zhang, Q.B.; Zhao, J.
Highlights: Grain scale discrete element model is proposed to study dynamic properties of rocks. Heterogeneous rocks are reproduced and micro fracturing characteristics are investigated. Rocks behave fragmentation transition from sparse fracture to pervasive pulverization as the strain rate increased. Strain rate mechanism is related to micro fracturing transition from intergranular to transgranular. Abstract: The dynamic tension behaviours of granites are tested with the split Hopkinson pressure bar and the quasi-static responses including the compression and Brazilian splitting are carried out with a material testing system. The experimental results show the tensile strengths behave significant strain rate effect. In order to characterize the realistic fracturing process from the viewpoint of grain scale failure, a multiple scale discrete element model considering the micro heterogeneity is proposed using the digital image processing of mineral scanning for rocks. Comparison of the experimental and numerical tension stress as well as the ultimate fragment state indicates the grain-based model is reasonable in simulation of dynamic tension test on granites. Then the three-wave superposition, crack propagation sequences, end forces and the stress distribution are discussed to confirm the stress equilibrium in the specimen. Using the microheterogeneous model, the micro fracturing process and fragmentation in association with energy dissipation at different strain rates are discussed. It is found that the failure sequence can be divided into five stages as crack initiation, propagation, coalesce, branching and indentation crush on the stress curve in dynamic loading. The intrinsic mechanism of the strain rate effect is believed to be the transitions of the micro fracturing type, orientation and the damage degree in the specimen and in turn exhibiting more energy dissipation as well as fragmentation transition from sparse fracture to pervasive pulverization. Finally, the scaling model of the dynamic increase factor for granite is derived and the characteristic strain rate, increase rate factor values are discussed.